The Analysis of the Meaning in The Poem Fire and Ice by Robert Frost - Yuliana, Putu Ninda (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to analyze the prose meaning and the total meaning contained in the poem “Fire and Ice” by Robert Frost. The writer relates other intrinsic elements (Symbol, Paradox, Denotation, and Connotation) to support and strengthen the meaning contained in the poem “Fire and Ice”. The intrinsic elements that used have also been analyzed. After the writer analyzes all these elements, the elements are interrelated to form a poem. Something that makes this poem interesting is that all the elements discussed are able to support the meaning of the poem and interconnected to form a unified meaning. By knowing these elements, we can capture the whole meaning of the poem.